Multiscale Organization of Neural Networks in a 3D Bioprinted Matrix - Huiyu Yang; Jiangang Zhang; Yiran Li; Zihan Zhong; Wenhua Li; Haojun Luo; Yanyong Liu; Liujian Ouyang; Zhuoran Jiang; Yuning Sun; Hang Sun; Lulu Liu; et al. (Advanced Science)
Abstract The efficient establishment of in vitro neural models that accurately mimic the structural and functional connectivity of neural networks is critical in neuroscience research. 3D bioprinting shows great potential for constructing sophisticated in vitro models with high freedom of design. However, mature neurons are delicate and susceptible to manipulation. Here, extrusion‐based 3D bioprinting is employed to fabricate gelatin methacryloyl (GelMA)‐based constructs containing embryonic day 18 (E18) rat cortical neurons, referred to as 3D neuMatrix. 3D neuMatrix displays favorable neuronal viability, with the progressive formation of a 3D brain‐like neural network with local and long‐range functional axon connections. Compared with 2D cultured neurons, 3D neuMatrix is more similar to the E18 cortex according to the bulk transcriptomic profile, with a recreation of cellular components in the cerebral cortex. The 3D neuMatrix is employed to establish a disease model of ischemic stroke, with a faithful recapitulation of the viability, function, and transcriptomic features of rats with middle cerebral artery occlusion/reperfusion (MCAO/R). These findings demonstrate the formation of multiscale neural circuits within 3D neuMatrix and its valuable potential in the study of neurodevelopment, disease modeling with drug screening, and in vitro intelligence.